A decade of Ghana : politics, economy and society, 2004-2013 - Amoah, Michael. (Middle East and Islamic Studies E-Books Online, Collection 2016, ISBN: 9789004303935., 2015)
This chronology for 2004 to 2013 compiles the chapters on Ghana previously published in the Africa Yearbook. Politics, Economy and Society South of the Sahara . Political stability in Ghana in the last few years contrasted with dramatic developments in other West-African countries. Ghana has a relatively high growth-rate, and also plays a role in regional security issues.